A Novel qPCR Method for Simultaneous Detection and Quantification of Viable Pathogenic and Non-pathogenic Vibrio parahaemolyticus (tlh+, tdh+, and ureR+) - Niu, Ben; Hong, Bin; Zhang, Zhaohuan; Mu, Lili; Malakar, Pradeep K.; Liu, Haiquan; Pan, Yingjie; Zhao, Yong (Frontiers in Microbiology, 2018)
Pathogenic and non-pathogenic Vibrio parahaemolyticus strains were simultaneously detected and quantified using a novel viable multiplex real-time PCR (novel qPCR). We used a new PCR primer and probe, ureR, as a surrogate for detection of the toxin trh gene as the primer was better at identifying variant V. parahaemolyticus trh strains. The specificity of all primers and probes used in this study were validated on three standard strains of V. parahaemolyticus, 42 clinical strains, 12 wild strains, 4 strains of Vibrio spp., and 4 strains of other bacteria. Then, propidium monoazide (PMA) was applied to inhibit DNA of dead cell, and the results of PMA optimized treatments were 15 μM concentration, 5 min incubation periods, 15 min light exposure periods and 30 RPM rotational speed, which resulted in time and cost savings. Pathogenic and non-pathogenic strains were quantified using a two-reaction tube method where the tlh, tdh, and ureR genes were amplified. Additionally, standard curves with a 7-log dynamic range were generated for quantifying viable V. parahaemolyticus and the amplification efficiencies were 108.68, 105.17, and 115.61% for tlh+, tdh+, and ureR+. This novel qPCR accurately monitored V. parahaemolyticus contamination rates in shrimps (Penaeus vannamei) and clams (Ruditapes philippinarum) sampled from retail stores located in a major district in Shanghai. In conclusion, our assay can prioritize the detection and quantification of viable pathogenic V. parahaemolyticus and can prove to be a more effective tool for reducing infection risks from consumption of seafood in Shanghai.